MOSQUITO (DIPTERA: CULICIDAE) AS A BIOINDICATOR OF ENVIRONMENTAL HEALTH AND DISEASE OUTBREAK - Sugeng Juwono Mardihusodo (Jurnal Manusia dan Lingkungan, 2006)
Quality of public health isgreatly influenced by a lot of environmental factors, especially bioticfactors among wich is a group of hematophagus mosquitoes (Diptera:Culicidae) showing high competence as disease vector(s). The vectormosquitoes belong to different species of different genera: *Anopheles,Aedes, Culex*, and *Mansonia.*In hypersensitive individuals, mosquito bitesmay induce pain and itching on the skin where the mosquito suck blood,allergic dermatitis leads up to dermatosis, even persistently, causingnuisance. Through the mosquito bites, man may risk to being infected withpathogens causing Malaria, Dengue Haemorrhagic Fever (DHF), Chikungunya,Japanese Encephalitis (JE), and Lymphatic filariasis, specifically in areaswhere the mosquito-borne disease (MBD) is (are) endemic. Survival of amosquito vector species of disease vector is much dependent on itsenvironment, mainly on the availability of a number of suitable habitatsfor its pre-adult stages, larvae and pupae. Number, type and size of thelarval habitats as well as quality of water in the mosquito breeding placesapparently determine rates of survival and density of the mosquito breedingin it which generally positively correlate with the increase of the MBDtransmission. Therefore, mosquito mainly a disease vector could be used asone of the bioindicators of environment health and its significant increasein density is predictive of the probable occurrence of a MBD epidemic in acommunityliving in an endemic area.